Inovasi Layanan Eazy Passport oleh Kantor Imigrasi Kelas I Tempat Pemeriksaan Imigrasi (TPI) Pekanbaru - Dhea Annisa; Mimin Sundari Nasution (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Eazy Passport Service Innovation is a passport service innovation with the reach out or ball pickup method initiated by the Directorate General of Immigration of the Ministry of Law and Human Rights of the Republic of Indonesia, to increase public service innovation, the number of passport issuances and PNBP revenue, which has been implemented by all immigration offices in Indonesia since the pandemic period until now. One of them is the Immigration Office Class I TPI Pekanbaru. This research is motivated by the problems, namely the lack of information provided during socialization, the limited human resources in the Eazy Passport Service Innovation by the Immigration Office Class I TPI Pekanbaru, and the issuance of passports that can take more than 4 working days. The purpose of this research is to find out the Eazy Passport Service Innovation by the Immigration Office Class I TPI Pekanbaru and to identify the inhibiting factors of the Eazy Passport Service Innovation by the Immigration Office Class I TPI Pekanbaru. The type of research used is a qualitative research method with a descriptive approach, where data collection techniques are carried out through observation, interviews and documentation. The results showed that the Eazy Passport Service Innovation by the Class I TPI Immigration Office Pekanbaru is still not fully running optimally, although on the other hand it also received appreciation from several passport applicants. The inhibiting factors in the Eazy Passport Service Innovation by the Class I TPI Immigration Office Pekanbaru, namely an unstable network at the location of the implementation and system errors, limited human resources and lack of understanding and knowledge of the applicant community in processing passports.